A model for paddy industry in Malaysia - Idris, Nurjihan; Shamsudin, Mad Nasir; Mohamed Arshad, Fatimah; Alias, Emmy Farha (School of Social Sciences, Universiti Sains Malaysia, 2012)
This study is conducted to analyze the factors affecting the paddy industry in Malaysia. The findings indicate that on the supply side, the estimated result shows that fertilizer subsidy and technology are important determinants in estimating paddy yield. Fertilizer subsidy and technology should be focused as one of the key issues in paddy is low yield. Meanwhile, on the demand side, price elasticity of demand is inelastic. This shows that consumers are not responsive to change in price of rice. On the other hand, income elasticities show rice is inferior good.